VALORIZATION OF WASTE COOKING OIL INTO BIODIESEL OVER COMPOSITES SBA-15-SO3H/PVA CATALYSTS - Castanheiro, J (2016)
Waste cooking oil (WCO) was converted into biodiesel with methanol over a composites catalyst consisting in SBA-15 with sulfonic acid groups (SBA-15-SO3H) immobilized in poly (vinyl alcohol) (PVA), at 60ºC. It was observed that the catalytic activity increased with the amount of SBA-15-SO3H dispersed in PVA. The catalytic stability of [SBA-15-SO3H]3/PVA. composite was studied. A good stability was observed.